The Struggle to Make CNS Axons Regenerate: Why Has It Been so Difficult? - Fawcett, James W (Neurochemical research, 2020)
Axon regeneration in the CNS is inhibited by many extrinsic and intrinsic factors. Because these act in parallel, no single intervention has been sufficient to enable full regeneration of damaged axons in the adult mammalian CNS. In the external environment, NogoA and CSPGs are strongly inhibitory to the regeneration of adult axons. CNS neurons lose intrinsic regenerative ability as they mature: embryonic but not mature neurons can grow axons for long distances when transplanted into the adult CNS, and regeneration fails with maturity in in vitro axotomy models. The causes of this loss of regeneration include partitioning of neurons into axonal and dendritic fields with many growth-related molecules directed specifically to dendrites and excluded from axons, changes in axonal signalling due to changes in expression and localization of receptors and their ligands, changes in local translation of proteins in axons, and changes in cytoskeletal dynamics after injury. Also with neuronal maturation come epigenetic changes in neurons, with many of the transcription factor binding sites that drive axon growth-related genes becoming inaccessible. The overall aim for successful regeneration is to ensure that the right molecules are expressed after axotomy and to arrange for them to be transported to the right place in the neuron, including the damaged axon tip.
Keywords: Schwann cell; Animals; Neurogenesis; NogoA; nervový útlum; proteosyntéza; axony; Integrins; neurogeneze; Chondroitinase; Neural Inhibition; Epigenetics; Signalling; lidé; Axons; Trafficking; Chondroitin sulphate proteoglycans; PTEN; Axon regeneration; regenerace nervu; Central Nervous System; Nerve Regeneration; Axonal transport; Rabs; RhoA; Protein Biosynthesis; Axonal Transport; zvířata; centrální nervový systém; axonální transport; Humans